NOISE IN LARGE PRODUCTION ENTERPRISES, ITS IMPACT ON THE HEALTH OF WORKERS AND METHODS OF COMBATING NOISE - H. Pakhirdinov; A.Normirzayev; M. Toragulov (Journal of Geography, Regional Planning and Development, 2024)
Industrial production is one of the main areas of economic development of any country, so it is worth saying that large factories play a very important role in achieving high productivity. Large production enterprises are important in meeting the demands and needs of society